Comparison between Vascular Endothelial Growth Factor and Platelet-Derived Growth Factor Levels in Rhegmatogenous Retinal Detachment. (6th December 2021) - Ichsan, Andi Muhammad; Windy, Dyah Ayu; Muhiddin, Habibah Setyawati; Budu,; Massi, Muhammad Nasrum; Islam, Itzar Chaidir
Abstract : Introduction . This study aimed to assess vascular endothelial growth factor (VEGF) and platelet-derived growth factor (PDGF) levels within vitreous and blood serum samples of patients with rhegmatogenous retinal detachment (RRD) and their relationship to the development of proliferative vitreoretinopathy (PVR). Methods . Seventeen eyes of patients with RRD were included in the RRD group and divided into three subgroups: RRD without PVR, RRD with PVR grades A and B, and RRD with PVR grade C. Five control eyes (nucleus and intraocular lens drop) were included in this study. Blood serum and vitreous samples were collected during vitrectomy. VEGF-A and PDGF-AA levels were determined by enzyme-linked immunosorbent assay. Results . The mean vitreous VEGF-A level in the RRD group was 131.71 ± 58.25 pg/mL, and the mean vitreous PDGF-AA level was 174.62 ± 65.17 pg/mL. Both levels were significantly higher in the RRD group compared with the control group (p < 0.05 ). Vitreous VEGF-A and PDGF-AA levels were the highest in RRD with PVR grade C subgroup, with mean levels of 179.87 ± 21.02 pg/mL and 229.44 ± 14.09 pg/mL, respectively (p < 0.05 ). The vitreous VEGF-A/PDGF-AA ratios in the RRD subgroups were completely different. Conclusion . Based on the tendency of VEGF-A and PDGF-AA levels, RRD surgery has to be performed as soon as possible prior to retinal cell death and membrane proliferative formation.